School Leaders and Inclusive Education in Peru : A Case Study of Principal Leadership in an Effective Inclusive School - Valdivieso, Pamela (2020)
Since the adoption of the inclusive education (IE) approach, the Peruvian Ministry of Education has made improvements to the normative regarding special educational needs (SEN) students. However, implementing this reform continues to present numerous challenges. A recent study of the IE policy, conducted in 2016, concluded that the key problem was the lack ofsensitization and low training of school leaders and teachers which prevented them from providing a better educational service to SEN students. The evidence that links the role of principal leaders and IE is almost non-existent in the Peruvian context. Therefore, this qualitative case study seeks to fill this research gap by exploring the challenges, strategies, and training needs of school leaders in an inclusive school in Peru. The study was conducted in a school with a high performing school leader where it was believed that a more positive environment towards reform implementation could be found. Interview data was collected from school leaders, the administrative support staff, and teachers. The findings of this research work conclude that the selected school has been significantly successful in implementing the reform by promoting inclusive values within the school, working with the school community to improve school climate for inclusion, and developing professional learning communities to develop pedagogical strategies for inclusive teaching. This research provides important inputs for the design and implementation of leadership policies and preparation programs with attention to students with disabilities.